Seasonal Knowledge and the Almanac Tradition in the Arab Gulf - Varisco, Daniel Martin. author. aut Link
XXIV, 446 p.
Keywords: This book is the first in English to survey indigenous knowledge of seasonal, astronomical, and agricultural information in Arab Gulf almanacs. It provides an extensive analysis of the traditional information available, based on local almanacs, Arabic texts and poetry by Gulf individuals, ethnographic interviews, and online forums. A major feature of the book is tracing the history of terms and concepts in the local seasonal knowledge of the Gulf, including an important genre about weather stars, stemming back to the ninth century CE. Also covered are pearl diving, fishing, seafaring, and pastoral activities. This book will be of interest to scholars who study the entire Arab region, since much of the lore was shared and continues through the present. It will also be of value to scholars who work on the Indian Ocean and Red Sea Trade Network, as well as the history of folk astronomy in the Arab World. Daniel Martin Varisco is an anthropologist and historian with research experience in Yemen, Egypt and the Arab Gulf. He has written about Arabic folk astronomy and astrology, traditional agriculture and the history of the Arab almanac. He is currently President of the American Institute for Yemeni Studies.